Structural and mechanistic consequences of polypeptide binding by GroEL - Coyle, J; Jaeger, J; Gross, M; Robinson, C; Radford, SE (1997)
The remarkable ability of the chaperonin GroEL to recognise a diverse range of non-native states of proteins constitutes one of the most fascinating molecular recognition events in protein chemistry. Recent structural studies have revealed a possible model for substrate binding by GroEL and a high-resolution image of the GroEL-GroES folding machinery has provided important new insights into our understanding of the mechanism of action of this chaperonin. Studies with a variety of model substrates reveal that the binding of substrate proteins to GroEL is not just a passive event, but can result in significant changes in the structure and stability of the bound polypeptide. The potential impact of this on the mechanism of chaperoninassisted folding is not fully understood, but provides exciting scope for further experiment. © Current Biology Ltd.